2023
DOI: 10.1021/acsomega.3c05849
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Ultrasound-Compatible Microfluidic Platform for In Vitro Microvasculature Flow Research and Imaging Optimization

Tamar Mano,
Tal Grutman,
Tali Ilovitsh

Abstract: Ultrasound localization microscopy (ULM) enables the creation of super-resolved images and velocity maps by localizing and tracking microbubble contrast agents through a vascular network over thousands of frames of ultrafast plane wave images. However, a significant challenge lies in developing ultrasound-compatible microvasculature phantoms to investigate microbubble flow and distribution in controlled environments. In this study, we introduce a new class of gelatin-based microfluidic-inspired phantoms unique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…We recently showed that molecule extravasation following MB-mediated BBBD is reduced in capillaries 8 . It is likely due to a combination of effects, including constrained oscillations alongside smaller numbers of MBs within these capillaries, compared to larger arteries 911 . This scenario becomes more complex when considering the inherent heterogeneous diameters of brain vasculature, ranging from capillaries to arteries, which leads to variations in BBBD as a function of blood vessel diameter and can potentially inhibit desired therapeutic results in smaller vessels 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…We recently showed that molecule extravasation following MB-mediated BBBD is reduced in capillaries 8 . It is likely due to a combination of effects, including constrained oscillations alongside smaller numbers of MBs within these capillaries, compared to larger arteries 911 . This scenario becomes more complex when considering the inherent heterogeneous diameters of brain vasculature, ranging from capillaries to arteries, which leads to variations in BBBD as a function of blood vessel diameter and can potentially inhibit desired therapeutic results in smaller vessels 12,13 .…”
Section: Introductionmentioning
confidence: 99%